Dimensions of Muslim unity in Russia, 1905-1917 - Akhmetova, Elmira (Hartford Seminary, 2019)
This article presents a general outline of the ideas of Muslim unity in Russia at the beginning of the twentieth century, its aims, scope, and dimensions. The Russian Revolution of 1905 had significantly stirred the ambitions of Russia’s Muslims for unity and progress, the very ideas which were buried in their hearts for centuries due to the ruthless colonial policies of the empire. Russia’s Muslim intelligentsia and middle-class enthusiastically founded a far-reaching movement for renewal and regeneration (iṣlāḥ and tajdid) with a great emphasis on ideas of unity, which consisted of calling nationwide congresses of Muslims, participation in policy-making process of the empire, educational and social reforms, and the advancement of the Muslim printing press. The Muslim masses named the entire development with the term Ittifāq while the educated circles used the term ittihād al-Islām to express the idea of Islamic unity. In imperial records, the terms ‘pan-Islamism’ and ‘pan-Turkism’ were interchangeably used to describe the entire social, political, religious, educational, cultural and economic awakening of Russia’s Muslims in that particular period. This article consequently suggests that the notions of ‘pan-Islamism’ and Ittifāq bear a broader meaning in the case of Russia, embracing a large-scale movement of the socio-political and religio-cultural awakening of its Muslim population in the first three decades of the twentieth century. This contention is based on textual analysis of the official documents from Tsarist and Soviet sources, records of the All-Russian Muslim Congresses between 1905 and 1918, as well as the thoughts and activities of Russia’s Muslim intellectuals, such as ‘Abd al-Rashīd Ibrahimov (1857-1944), Musa Jārullāh (1875-1949) and Ismail Gaspralı (1851-1914). The article indicates that Ittifāq was a peaceful movement primarily with a religious and cultural orientation towards the spiritual unity of Muslims. Lastly, the study concludes that pan-Islamism in the case of Russia did not bear aggressive facets; rather, Muslims sought to reform their societies through educational and peaceful means.